Simvastatin and hormone replacement in postmenopausal high cholesterol - (:unkn) unknown (My University, 2000)
In this study, we gave 100 postmenopausal hypercholesterolemic women either simvastatin alone or in combination with hormone replacement therapy (estrogen and medroxyprogesterone). The results suggested that combination therapy is more effective at lowering total and low-density lipoprotein cholesterol and raising high-density lipoprotein cholesterol than simvastatin alone.